ANALYSIS OF MEDIA DEVELOPMENT NEEDS E-MAGAZINE MATERIAL INHERITANCE OF ISLAMIC INTEGRATED NATURE FOR GRADE IX STUDENTS AT ISLAMIC JUNIOR HIGH SCHOOL - Pertiwi Adi Puji Astuti; Mukhlis Rohmadi; Ridha Nirmalasari (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2022)
This research to conduct an analysis of the need to design science learning media. Needs analysis is done through interviews with teachers and students and field studies. The analytical technique used is qualitative descriptive analysis. The results of the interview concluded that 1) The use of learning media as a learning resource in the science learning process is limited to student worksheets books and modules, making it less attractive to students. 2) The learning process is only focused on the lecture method, so students are less active in the learning. The results of the teacher's needs analysis stated that 100% agreed to use e-magazine learning media of nature inheritance material. The results of the analysis of student is 92.7% of students stated the need for media development, 52.7% of students stated that the material inheritance of nature is difficult to understand, 67.3% of students want interesting, illustrative and easy to understand learning media and 94.5% of students stated that they agreed to develop learning media in the form of e-magazine nature inheritance material and 63.6% of students expressed the need to understand It is a learning process with Islamic integration.